PENGARUH MEDIA PEMBELAJARAN KAHOOT TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV SDN 32 CAKRANEGARA - Wahyu, Yuyun; Suhadah; Ulfaturrahmah; Intan Dwi Hastuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the effect of kahoot learning media on the learning motivation of fourth grade students of SDN 32 Cakranegara 2024/2025. This research is included in quantitative research using experimental methods. The population and sample in this study totalled 46 students with a control class of 23 students and an experimental class of 23 students. From the results of the written tests that the researchers conducted, there were student scores in the experimental class with the highest pre-test score of 85 and the lowest score of 45 in the post-test with the highest score of 100 and the lowest score of 60, while in the control class the highest pre-test score was 80 and the lowest score was 45 in the post-test with the highest score of 80 and the lowest score of 50. Data collection techniques used critical thinking ability tests in the form of multiple choice and descriptions. The results showed that the results of the hypothesis test showed a significance value obtained of 0.000 which means that 0.000 < 0.05, then rejected and accepted. So, it means that there is a difference in the average value of students taught by using kahoot learning media on student learning motivation.